ANALISA YURIDIS PENGGELAPAN DANA PADA BANK PERMATA : STUDI PUTUSAN PENGADILAN NEGERI KENDARI NO. 568/PID.B/2021/PN.KDI - Prasetya, Zaki Ismu; Waluyo, Waluyo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The Abdi Rahman case is a clear example of the problem of embezzlement of funds that often occurs in Indonesia. Abdi Rahman, an employee of PT. Permata Finance Indonesia, was proven to have embezzled company funds amounting to Rp. 61,599,000,-. Abdi Rahman’s actions violated Article 374 of the Criminal Code concerning the crime of embezzlement in office. This research aims to analyze the case of embezzlement of Abdi Rahman’s funds from the perspective of Indonesian criminal law. This research uses normative legal research methods with a conceptual approach. Research data was obtained from literature studies, court decisions, and relevant laws and regulations. The results of the research show that Abdi Rahman was legally and convincingly proven to have committed the crime of embezzlement in office as regulated in Article 374 of the Criminal Code. The judge sentenced Abdi Rahman to 6 (six) months in prison as a form of accountability for his actions. This research also shows that criminal liability in cases of embezzlement of funds is determined by several factors, namely: the fulfillment of the elements of the crime of embezzlement of funds, evidence of the defendant’s malicious intent, and the losses incurred